Little house on the prairie - Wilder, Laura Ingalls, 1867-1957.; Williams, Garth (New York : HarperTrophy, 1971)
A family travels from the big woods of Wisconsin to a new home on the prairie, where they build a house, meet neighboring Indians, sink a well, and fight a prairie fire.
Keywords: Frontier and pioneer life -- Fiction; Families -- Fiction